FDP/fibrinogen ratio reflects the requirement of packed red blood cell transfusion in patients with blunt trauma - Hagiwara, Shuichi; Aoki, Makoto; Murata, Masato; Kaneko, Minoru; Ichikawa, Yumi; Nakajima, Jun; Isshiki, Yuta; Sawada, Yusuke; Tamura, Jun'ichi; Oshima, Kiyohiro (The American journal of emergency medicine, 2017)
To find factors that predict the requirement of packed red blood cells (pRBC) transfusion in patients with blunt trauma on arrival at the hospital. We conducted blood tests in trauma patients whose trauma severity was suspected as being 3 and over in the Abbreviated Injury Scale. Patients were divided into the blood transfusion (BT) and control groups according to the requirement of pRBC transfusion within 24h after arrival. We analyzed 347 patients (BT group, n=14; control group, n=333). On univariate analysis, there were significant differences in Glasgow Coma Scale (GCS), rate of positive FAST (focused assessment with sonography for trauma) finding, hematocrit, international normalized ratio of prothrombin time, activated partial thromboplastin time, fibrinogen (Fib), and level of fibrin degradation products (FDP). On multivariable analysis, positive FAST finding, GCS, Fib, and FDP influenced the requirement of pRBC transfusion. In the area under the receiver operating characteristic curve analysis, Fib and FDP were markers that predicted the requirement of pRBC transfusion. The FDP/Fib ratio had a better correlation with the requirement of pRBC transfusion than FDP or Fib. The FDP/Fib ratio can be easily measured and may be a predictor of the need for pRBC transfusion.